2016
DOI: 10.1126/science.aag1125
|View full text |Cite
|
Sign up to set email alerts
|

Integration of omic networks in a developmental atlas of maize

Abstract: Coexpression networks and gene regulatory networks (GRNs) are emerging as important tools for predicting functional roles of individual genes at a system-wide scale. To enable network reconstructions, we built a large-scale gene expression atlas composed of 62,547 messenger RNAs (mRNAs), 17,862 nonmodified proteins, and 6227 phosphoproteins harboring 31,595 phosphorylation sites quantified across maize development. Networks in which nodes are genes connected on the basis of highly correlated expression pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
483
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 412 publications
(547 citation statements)
references
References 45 publications
28
483
3
Order By: Relevance
“…Moderately positive correlations between transcriptome and proteome data are usual and have been reported previously (Maier et al, 2009). In a recent study in maize (Zea mays), similar correlations values were observed, but enrichment categories were found to be highly similar between transcriptome and proteome data (Walley et al, 2016). The enrichment analysis (see Supplemental Data Set 6) points to a similar trend.…”
Section: Other -Omics Data Processing and Statistical Analysissupporting
confidence: 83%
“…Moderately positive correlations between transcriptome and proteome data are usual and have been reported previously (Maier et al, 2009). In a recent study in maize (Zea mays), similar correlations values were observed, but enrichment categories were found to be highly similar between transcriptome and proteome data (Walley et al, 2016). The enrichment analysis (see Supplemental Data Set 6) points to a similar trend.…”
Section: Other -Omics Data Processing and Statistical Analysissupporting
confidence: 83%
“…and function of a protein of interest. However, many researchers had found inconsistencies between mRNA and protein level (Baerenfaller et al, 2008;SchwanhĂ€usser et al, 2011;Ponnala et al, 2014;Walley et al, 2016). Although relatively fewer protein expression data are available, these data are amenable to GCN construction and could represent a more direct reflection of interacting proteins.…”
Section: The Performance Of Protein Network Did Not Exceed Aggregatimentioning
confidence: 99%
“…S2). Several network studies from plant RNA-Seq data used log2 transformation (Davidson et al, 2011;Ma and Wang, 2012;Giorgi et al, 2013;Stelpflug et al, 2016;Walley et al, 2016). In our analysis, genes with CPM greater than 2 in more than 1000 samples were included.…”
Section: Manually Curated Maize Mrna Expression Profiling From Publicmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the phylogenetic tree is not proportional to the phylogenetic distance. those in nonsyntenic regions (Walley et al 2016). We tested the hypothesis that AS and conserved AS is enriched in syntenic vs. nonsyntenic regions across the grass species.…”
Section: As Conserved Between Monocot Grass and Nongrass Speciesmentioning
confidence: 99%